2021
DOI: 10.1038/s41419-020-03280-5
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 uses STAT3-mediated slug expression to maintain radioresistance of non-small cell lung cancer cells: emerges as a potential prognostic biomarker for lung cancer

Abstract: Lung cancer is one of the most common reasons for cancer-induced mortality across the globe, despite major advancements in the treatment strategies including radiotherapy and chemotherapy. Existing reports suggest that CXCR4 is frequently expressed by malignant tumor and is imperative for vascularization, tumor growth, cell migration, and metastasis pertaining to poor prognosis. In this study, we infer that CXCR4 confers resistance to ionizing radiation (IR) in nonsmall cell lung cancer (NSCLC) cells. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…During the DSB resulted from various factors, H2AX is phosphorylated into g-H2AX, which, thus, has been taken as an indicator for DNA damage and repair, and its upregulation indicated the exacerbation of DNA damage. 40,41 In our study, we found that the knockout of PAK7 in HCC cells could further increase the IR-induced expression of g-H2AX, which could indirectly implied that PAK7 might reduce the DSB of DNA in HCC cells and accelerate the repair of DNA damage, thereby weakening the sensitivity of cells to radiotherapy. Irradiationassociated DNA damage can lead to G2/M checkpoint activation and consequent G2/M phase arrest, enabling DNA repair to occur prior to cellular entry into mitosis.…”
Section: Discussionmentioning
confidence: 65%
“…During the DSB resulted from various factors, H2AX is phosphorylated into g-H2AX, which, thus, has been taken as an indicator for DNA damage and repair, and its upregulation indicated the exacerbation of DNA damage. 40,41 In our study, we found that the knockout of PAK7 in HCC cells could further increase the IR-induced expression of g-H2AX, which could indirectly implied that PAK7 might reduce the DSB of DNA in HCC cells and accelerate the repair of DNA damage, thereby weakening the sensitivity of cells to radiotherapy. Irradiationassociated DNA damage can lead to G2/M checkpoint activation and consequent G2/M phase arrest, enabling DNA repair to occur prior to cellular entry into mitosis.…”
Section: Discussionmentioning
confidence: 65%
“…We previously demonstrated an association between CXCL12/CXCR4 signaling and gemcitabine resistance in gemcitabine-resistant PaCa cell lines ( 32 ). In addition, CXCR4 may be involved in radiation resistance in colorectal cancer ( 50 ), thyroid cancer ( 51 ), and non-small cell lung cancer ( 52 ). We established radiation-resistant PaCa cell lines to investigate the factors involved in the radiation resistance of PaCa.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is a central regulator of tumor immune tolerance. Importantly, STAT3 can act as a negative feedback regulator, and targeted inhibition of STAT3 can enhance the efficacy of radiotherapy for head and neck cancer [ 48 ], lung cancer [ 49 ], and breast cancer [ 50 ]. Studies have shown that transcription factor ZNF341 is a positive regulator of STAT3 expression [ 51 ].…”
Section: Discussionmentioning
confidence: 99%